Blockchain Technology as a Security Layer for Sharing Large Files - Shukur, Nihad (ADA University, 2023)
In today’s digitally-driven world, exchanging and preserving private files has grown into a crucial aspect of our daily routines. Both enterprises and individuals regularly send and obtain confidential papers, pictures, and various data formats. Nevertheless, guaranteeing the safety and confidentiality of these files is a major challenge. Conventional file-sharing techniques frequently encounter difficulties such as security breaches, unauthorized entry, and manipulation. These obstacles call for the creation of a robust, decentralized, and impervious framework for the dissemination of delicate materials. The focal point of this master’s dissertation is devising a dependable file-sharing platform, which is built upon the foundation of blockchain technology. Blockchain, a decentralized and distributed ledger system, guarantees the preservation of data authenticity, safety, and openness. This technology carries the capacity to bring about a significant shift in file-sharing practices by delivering a protected, stable, and invulnerable platform for the storage and exchange of confidential information. The core aim of this research is to conceptualize, execute, and assess a safe filesharing platform grounded in blockchain technology. This platform will empower users to securely and privately exchange sensitive files, eliminating the need for a central authority. The specific goals of this study include: Performing an exhaustive literature review encompassing blockchain technology and its uses in the realm of secure file sharing. Creating a safe and decentralized file-sharing platform, utilizing the Python programming language and the Flask web framework. Employing cryptographic methods to guarantee the confidentiality, integrity, and authenticity of the exchanged files. Evaluating the efficiency, security, and user-friendliness of the developed platform through a series of tests and analyses.
Keywords: Blockchain technology -- Applications in file sharing.; Data privacy -- Blockchain solutions.; Web development -- Blockchain integration.; Flask (Web framework) -- Applications in security.; Secure communications -- Blockchain-based platforms.; IT and Engineering